Perancangan Buku Cerita Pop-Up Berbasis Karakter untuk Menanamkan Karakter Peduli Sosial Anak Usia Dini - Luthfatun Nisa; Wuri Wuryandani; Mayang Masradianti (International Consortium of Education and Culture Research Studies, 2018)
Social awareness (Caring) is one of the important character implanted in early childhood as the basic foundation for the development of other characters. Therefore, efforts to introduce and plant it is important. One of them through storytelling activities by using media that appeal to children. This study aims to acquire, collect, analyze information and data used as a reference in the design of an interesting storybook media that is pop-up developed with the character base. Especially to instill the character of social caring in accordance with the needs of the field. This research method used field observation and also interview with Kindergarten teachers in Sewon Bantul Yogyakarta. Based on the results of observations and interviews found the results that children are more interested in the storybook with a more realistic appearance and can move the pop-up but the contents of the pop-up book that there is not much that contains the content of planting characters especially social caring. So with the doing of this media design is expected to be a solution and facilitate teachers to instill social care characters in early childhood and social character of children can develop well.